"Achieving a healthy baby": The online representations of embryonic screening and diagnosis by Spanish fertility clinics - Otín-Gavín, Jorge; Hüttel, Astrid Boe; Turrini, Mauro (Revista de Antropología Social, 2026)
Embryonic genetic testing consists of two distinct techniques: The Preimplantation Genetic Diagnosis (PGD/PGT-M & PGT-SR) and Preimplantation Genetic Screening (PGS/PGT-A). While PGD is used in cases where people are known to be carriers of a genetic disease they wish to avoid transferring to their offspring, PGS is offered to “healthy” people undergoing in vitro fertilization (IVF) in order to increase the success rates of the fertility treatment. This article takes its point of departure in this distinction between “diagnosis” and “screening” in order to analyze the discourses on embryo selection that Spanish fertility clinics (re)produce through their means of online communication. The constant confusion between these techniques identified in the empirical material is interpreted as the symptom of a transformation within the field of Assisted Reproductive Technologies (ARTs), in which the aim is no longer limited to the creation of babies, but rather “healthy” babies.